The Evolution of Regret: Decision Making for Parents of Children with Cancer - Sisk, Bryan A. (Support Care Cancer, 2019)
PURPOSE: Parents of children with cancer make treatment decisions in highly emotional states while feeling overwhelmed with information. In previous work, 1 in 6 parents demonstrated heightened decisional regret regarding treatment at diagnosis. However, it is unclear how regret evolves over time. We aimed to determine whether parents of children with cancer experience decisional regret over time, and to identify parental characteristics and clinician behaviors associated with longitudinal regret. METHODS: Prospective, questionnaire-based cohort study of parents of children with cancer at two academic pediatric hospitals. Parents reported decisional regret at diagnosis, 4 months and 12 months. RESULTS: At baseline, 13% of parents (21/158) reported heightened regret, 11% (17/158) at 4 months (p=.43, McNemar’s test relative to baseline) and 11% (16/158) at 12 months (p=.35 relative to baseline and p=.84 relative to 4 months). In multivariable analysis using generalized estimating equations adjusted for timepoint of survey completion, heightened regret was associated with non-white race/ethnicity (OR 11.57, 95% CI 3.53 to 41.05, p<.0001) and high anxiety (OR 2.01, 95% CI 1.04 to 3.90, p=.04). Parents with high peace of mind (OR 0.24, 95% CI 0.09 to 0.62, p=.003) and those reporting high quality information (OR 0.22, 95% CI 0.07 to 0.69, p=0.01) had lower odds of heightened regret. We found no association between heightened regret and time point of survey administration. CONCLUSIONS: A small, significant proportion of parents experience heightened regret throughout the first year of their child’s cancer treatment; non-white parents are at higher risk. Effective communication may protect against regret.